(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
This paper discusses the problem of identifying cycles in the stock market. On the basis of monthly data on thedevelopment of indices of eight selected exchanges in the period January 1998 –December 2012 sought to determine the existence of cycles. To determine the length and strength applied Hodrick-Prescott filter and harmonic analysis. Trend was isolated using a filter, and harmonic analysis was used to identify cycles. Data for the world stock exchanges indicate that a 5-7.5 year cycle, and the data for the local stock exchanges in Central Europe indicate the existence of cycles of 2.5-3 year.